2019
DOI: 10.1177/1363461518823933
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religion in Suicidal Behavior, Attitudes and Psychological Distress Among University Students: A Multinational Study

Abstract: The purpose of this study was to determine the associations between religion, suicidal behavior, attitudes and psychological distress in 5572 students from 12 countries by means of a self-report questionnaire. Our results showed that an affiliation with Islam was associated with reduced risk for suicide ideation, however affiliating with Orthodox Christianity and no religion was related to increased risk for suicide ideation. While affiliating with Buddhism, Catholic religion and no religion was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 38 publications
5
27
0
7
Order By: Relevance
“…Of note, majority of Khateebs revealed that stressful life circumstances and biosocial crises compatible with current researches could induce transient depression [66][67][68][69]. Furthermore, almost all Khateebs supported that the main reasons underlying suicide include both the fragile religious faith and mental illnesses, and other studies [70][71][72] partially supported these findings. One tenth of RMLs expressed that suicide and suicidal attempts never occurred in Saudi society that is not tenable [73][74][75].…”
Section: Discussionsupporting
confidence: 61%
“…Of note, majority of Khateebs revealed that stressful life circumstances and biosocial crises compatible with current researches could induce transient depression [66][67][68][69]. Furthermore, almost all Khateebs supported that the main reasons underlying suicide include both the fragile religious faith and mental illnesses, and other studies [70][71][72] partially supported these findings. One tenth of RMLs expressed that suicide and suicidal attempts never occurred in Saudi society that is not tenable [73][74][75].…”
Section: Discussionsupporting
confidence: 61%
“…All data were collected through self-administered questionnaire forms, which included items about nonfatal suicidal behavior, religious affiliation and strength of religious belief, attitudes towards suicide and towards suicidal individuals, and individualistic-collectivistic value orientations, alongside a measure of psychological distress. The prevalence of nonfatal suicidal behavior and psychological distress, attitudes towards suicide and suicidal persons, and the associations of religion with suicidal behavior and attitudes and psychological distress have been reported elsewhere (59)(60)(61). The focus of the present account is the associations of individualistic-collectivistic value orientations with suicidal behavior, suicidal attitudes, and psychological distress.…”
Section: Methodsmentioning
confidence: 82%
“…A further paper by Eskin et al. () on the role of religion on suicidal behaviour and attitudes found that an affiliation with Islam was associated with reduced risk for suicide ideation. However, affiliating with Orthodox Christianity and having no religion was related to increased risk for suicide ideation.…”
Section: Discussionmentioning
confidence: 98%
“…There is an increasing international interest in collaborative studies which focus on comparing students' attitudes, their prior experiences, judgements, perceptions of suicide, religiosity and cultural differences (Eskin, Kujan, et al., ; Eskin, Sun, et al., ; Eskin et al., , 2018). Three authors of these papers (LP, ME and CF) have contributed to this emerging body of work derived from 12 nations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation